Prestasi Kerja Protégés Ditinjau dari Fungsi Pementoran dan Kompleksitas Tugas - Stefani Lily Indarto (Forum Kerjasama Pendidikan Tinggi, 2022)
Performance appraisal serves as feedback for employees to improve their work performance, as well as assisting employees in preparing more appropriate career development programs for the benefit of their organization. But for new employees, of course, mentoring is needed in every assignment so that it can be carried out properly. This mentoring can help each new employee (protégés) and build interpersonal relationships between employees. In the Public Accounting Firm, auditor staff are also required to have good knowledge so that mistakes do not occur in giving audit judgments and completing audit assignments which are sometimes very complex. For this reason, a mentoring process is needed so that the new auditor staff can complete their field work. This study divides mentoring based on mentoring relationship activities, namely the training function, and the role modeling function and social support function and looks at the effect of task complexity on work performance produced by the auditor staff. Respondents in this study were external auditor staff who worked at KAP Semarang City who had experience working as junior auditors for less than 3 years. Data obtained by distributing questionnaires. From the research results it turns out that the training function, the role modeling function, and the social support function have a positive influence on the work performance of the proteges, but the task complexity has no effect on the work performance of the junior auditors. This study provides a broader picture of the benefits of mentoring for junior auditors, specifically which mentoring functions are effective in increasing the work performance of junior auditors.